Finding Mixed Cells in the Mixed Volume Computation - Li, T Y; Li, Xing (Foundations of computational mathematics, 2001)
In practice, finding mixed cells in certain polyhedral subdivisions plays a dominating role when a polyhedral homotopy is employed to approximate all isolated zeros of polynomial systems. This paper gives a new algorithm for the mixed cell computation via a new formulation of the underlying linear programming problems. Numerical results show that the algorithm provides a major advance in the speed of computation with much less memory requirements.[PUBLICATION ABSTRACT]